How Can Immune Checkpoint Inhibitors Cause Hyperprogression in Solid Tumors? - Denis, Morgane; Duruisseaux, Michael; Brevet, Marie; Dumontet, Charles (Frontiers in Immunology, 2020)
Following the administration of immune checkpoint inhibitors an unexpected pattern of response designated as hyperprogression may be observed in certain patients. This paradoxical response corresponds to an acceleration in tumor growth and a dramatic decrease of patient survival. The reported incidence rates of hyperprogressive disease are highly variable, ranging between 4% and 29%. In this review, we have performed a literature search on hyperprogressive disease, including both retrospective studies and case reports, and discuss potential predictive biomarkers as well as potential mechanisms associated with immune-checkpoint inhibitor associated hyperprogression.